Dampak Penggunaan Kredit Perbankan dan Pertumbuhan Industri Manufaktur terhadap Pertumbuhan Ekonomi Indonesia - Reza Anggapratama; Dwi Irnawati (Journal on Education, 2023)
The purpose of this study is to determine the impact of the use of bank credit and the growth of the manufacturing industry on economic growth in Indonesia. There are two independent variables, namely banking credit and the manufacturing industry, and the dependent variable, namely economic growth. This study uses a descriptive and quantitative approach to its methodology. The data used in this study is time series data covering the years 2011 to 2021. The data source was obtained through the Indonesian Central Bureau of Statistics and Banking Statistics. Multiple linear regression was used for the analysis of this study. Eviews 12 is the analytical tool used. The study findings show that the utilization of bank credit is a significant contribution to economic growth. In Indonesia, the manufacturing industry growth variable has a negligible impact on economic expansion.